Structural parameters defining distribution of collagen fiber directions in human carotid arteries - Fischer, Jiří; Heidrová, Aneta; Hermanová, Markéta; Bednařík, Zdeněk; Joukal, Marek; Burša, Jiří (Journal of the mechanical behavior of biomedical materials, 2024)
Collagen fiber arrangement is decisive for constitutive description of anisotropic mechanical response of arterial wall. In this study, their orientation in human common carotid artery was investigated using polarized light microscopy and an automated algorithm giving more than 4·106 fiber angles per slice. In total 113 slices acquired from 18 arteries taken from 14 cadavers were used for fiber orientation in the circumferential-axial plane. All histograms were approximated with unimodal von Mises distribution to evaluate dominant direction of fibers and their concentration parameter. 10 specimens were analyzed also in circumferential-radial and axial-radial planes (2-4 slices per specimen in each plane); the portion of radially oriented fibers was found insignificant. In the circumferential-axial plane, most specimens showed a pronounced unimodal distribution with angle to circumferential direction μ = 0.7° ± 9.4° and concentration parameter b = 3.4 ± 1.9. Suitability of the unimodal fit was confirmed by high values of coefficient of determination (mean R2 = 0.97, median R2 = 0.99). Differences between media and adventitia layers were not found statistically significant. The results are directly applicable as structural parameters in the GOH constitutive model of arterial wall if the postulated two fiber families are unified into one with circumferential orientation.
Keywords: Collagen; extracelulární matrix; kolagen; Biomechanical Phenomena; Stress, Mechanical; lidé; Humans; Algorithms; Arterial wall; biomechanika; Carotid artery; arteriae carotides; Collagen fiber direction; Extracellular Matrix; mechanický stres; adventicie; algoritmy; Adventitia; Histogram; Polarized light microscopy; Carotid Arteries